Beyond Spatial and Temporal Contingencies: Tantric Rituals in Eastern Central Asia under Tangut Rule, 11th–13th C. - Meinert, Carmen (Dynamics in the history of religions, 2022)
Tantric Buddhist ritual practice during the time of Tangut rule (ca. 1038-1227) in Eastern Central Asia can be studied on the basis of material, visual, and textual sources from various Buddhist sites. Here, I read a variety of sources that share a context to argue that a number of caves in the Northern Section of the Mogao Cave complex in Dunhuang were likely used for meditation and ritual practice, including as burial-meditation caves. These caves include Mogao Cave 465—the sole cave with an explicit Tantric Buddhist iconographic programme. I analyse the sources with the help of an analytical tool established by Knut Martin Stünkel, the three-level model of ‘transcendence-immanence distinction’ (TID), in order to understand the underlying ‘transcending process’, based on the ‘object-language level’ rather than on a specific notion of transcendence. Stünkel’s analysis is an outcome of an interdisciplinary research consortium at my home institution, the Center for Religious Studies (CERES) at Ruhr-Universität Bochum; thus, my chapter is an attempt to test the usefulness of the TID model for a medieval Central Asian Buddhist context. The application of this model allows one to analyse the process of the transformation of space, of the physical space of a ritual cave as well as of bodily space, as the practitioner’s perception of it is said to shift from an ‘immanent’ to a ‘transcendent’ perception. This would necessarily have an impact on the perception of time as well.